2019
DOI: 10.3389/fpsyg.2019.00997
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Not Attitudinal Factors Predict the Accuracy of Estimating Other Women’s Bodies in Both Women With Anorexia Nervosa and Controls

Abstract: Disturbance in how one’s body shape and size is experienced, usually including over-estimation of one’s own body size, is a core feature of the diagnostic criteria of anorexia nervosa (AN). Is this over-estimation specific to women with AN’s judgments of their own body? Or is it just a general feature of their judgments about all bodies? If the latter, it would be consistent with a general error in the perception of body size potentially linked to the use of a different set of visual cues for judging body size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…In nonclinical samples, it has been observed that bodies lower in weight than the population mean tend to be overestimated in terms of their weight and size, whereas larger bodies tend to be underestimated. This phenomenon, referred to as contraction bias, has been observed regardless of whether the body being judged belongs to another person (Gledhill et al, 2019) or the observer (Cornelissen, Bester, Cairns, Tovée, & Cornelissen, 2015; Cornelissen et al, 2016). The tendency of perceptual estimates to cluster around the mean of the stimulus set’s objective values has been described for over a century (Hollingworth, 1910; Stevens & Greenbaum, 1966).…”
Section: Other Perceptual Processesmentioning
confidence: 99%
“…In nonclinical samples, it has been observed that bodies lower in weight than the population mean tend to be overestimated in terms of their weight and size, whereas larger bodies tend to be underestimated. This phenomenon, referred to as contraction bias, has been observed regardless of whether the body being judged belongs to another person (Gledhill et al, 2019) or the observer (Cornelissen, Bester, Cairns, Tovée, & Cornelissen, 2015; Cornelissen et al, 2016). The tendency of perceptual estimates to cluster around the mean of the stimulus set’s objective values has been described for over a century (Hollingworth, 1910; Stevens & Greenbaum, 1966).…”
Section: Other Perceptual Processesmentioning
confidence: 99%
“…Consistent with previous studies where women estimated their own body size or other women’s body size [e.g., Refs. (27, 47, 49)], in the current study, plots of estimated body size are linearly predicted by the participant’s own actual BMI, but with a slope of less than unity (see the top two rows of Figure 3 ). Lower actual BMI participants over-estimate body size, middle-range actual BMI participants’ estimates are the most accurate, and high actual BMI participants under-estimate.…”
Section: Discussionmentioning
confidence: 48%
“…Thus, head motions elicited some changes in perspective due to motion parallax. Within this VR environment, participants were also able to rotate the 3D image to view it at the 45-degree or canonical view, as this angle has demonstrated improved accuracy in discriminating among bodies of different sizes [13,23,26]. Figure 2 shows examples of the silhouette (Sil), 2D textured (Tex), and 3D VR visualizations.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Piryankova et al [26] and Mölbert et al [3] generated morphed images that were ±5-20% BMI of the true image. Based on the concepts of contraction bias [13,37], participants would be biased toward selecting images in the middle of the presented range, this could thus bias responding accuracy (given that the real image was always the middle image). To mitigate this and to provide symmetry among the four test conditions, the images were confined within the range of 18-40 kg·m −2 as they were in the Pulvers' figure rating scale [5].…”
Section: Methodsmentioning
confidence: 99%